Enhancement‐Mode AlGaN/GaN Vertical Trench Metal–Insulator–Semiconductor High‐Electron‐Mobility Transistors with a High Drain Current Fabricated Using the AlGaN Regrowth Technique. Issue 7 (25th November 2019) - Yamamoto, Akio; Kanatani, Keito; Yoneda, Norifumi; Asubar, Joel T.; Tokuda, Hirokuni; Kuzuhara, Masaaki
Abstract : Herein, the first successful fabrication of enhancement (E)‐mode AlGaN/GaN vertical trench metal–insulator–semiconductor (MIS) high‐electron‐mobility transistors (HEMTs) using n + ‐GaN/p‐GaN/n − ‐GaN epistructures on free‐standing n + substrates is reported. A trench with smooth semipolar planes (sidewalls) with angles of 45° and 135° from the c ‐plane is formed by reactive ion etching. Using metalorganic vapor‐phase epitaxy, a uniform thickness of the AlGaN layer is regrown in the trench. Devices fabricated without Mg activation treatment for p‐GaN show depletion (D)‐mode operation. The operation mode is changed from D to E when Mg activation annealing temperature exceeds 700 °C. A high drain current ( I D ) ≥ 0.8 A mm −1 is obtained in the devices with a relatively low Mg concentration (≤1 × 10 18  cm −3 ), whereas a threshold voltage ( V TH ) as high as 22 V is obtained in the devices with a high Mg concentration (5 × 10 18  cm −3 ). The poorly controlled V TH with doped Mg concentration is discussed from the viewpoint of dehydrogenation of the p‐GaN layer. Abstract : E‐mode AlGaN/GaN vertical trench metal–insulator–semiconductor high‐electron‐mobility transistors (MIS HEMTs) are successfully fabricated using a regrown AlGaN layer. A high drain current ≥0.8 A mm −1 is obtained when a p‐GaN layer with a relatively low Mg concentration (≤1 × 10 18  cm −3 ) is used, whereas a threshold voltage of 22 V is obtained for p‐GaN with a high Mg concentration (5 × 10 18  cm −3 ).